Do patient bedside medicine lockers result in a safer and faster medicine administration round?. Issue 6 (13th July 2012) - Hogg, Anita; Scullin, Claire; Luo, Ruoyin; Currie, Andrew; Scott, Michael G; McElnay, James C
Abstract : Objective: To determine if the introduction of patient bedside medicine lockers leads to a safer and faster medicine administration round. Methods: The undisguised observer technique was utilised to observe the medicine administration round on four wards, two medical wards in Antrim Area Hospital (AAH) and two surgical wards in Causeway Hospital (CH), both before and after the introduction of patient bedside medicine lockers. All non-intravenous medicine administrations during the morning medicines administration round were observed and timed before and after the introduction of the lockers. Medicine administration errors (MAEs), time taken and reasons for delays were recorded and analysed. Results: The MAE rate and the time spent on the medicine administration round both decreased after the introduction of patient bedside medicine lockers. The MAE rate dropped from 8.3% to 1.3% (p < 0.001) in the AAH site and from 9.9% to 3.2% (p = 0.029) in the CH site; the time spent per patient on medicine administration decreased from 6.80 ± 5.44 min pre-intervention to 3.03 ± 1.87 min post-intervention and from 7.35 ± 6.24 min pre-intervention to 6.95 ± 5.39 min post-intervention in AAH (p < 0.001) and CH (p > 0.05), respectively. Conclusions: The introduction of patient bedside medicine lockers resulted in safer and faster medicine administration rounds.